The perception of heritage values and their analysis by using GIS tools in vernacular heritage landscapes - Pablo Altaba Tena (Vitruvio: International Journal of Architectural Technology and Sustainability)
The main objective of the study is to assess, independently of the scenic beauty, the importance and composition of the different attributes within a given landscape. For this purpose, the study focuses on Penyagolosa where we have selected three areas of evaluation to determine the importance of distance in the determination of heritage values of the landscape. Using Geographic Information Systems (GIS) determines what values are detectable on the basis of the terms of proximity and remoteness and how they are applied in three cases of assessment. Thus, 5 criteria have been set to analyze these values: 1. the overview of the landscape, 2. dominance or intensity of elements, 3. the aesthetic composition of space, 4. The selective interpretation of the visual and 5 variables. The fragility or alterations induced in the landscape. Ultimately, criteria are discussed from dynamic and static fields of the authenticity and integrity of the landscape and they affect how they neglect.